2013
DOI: 10.4314/ejesm.v6i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Procurement Performance of Traditional and Labour-Only Methods in Nigeria

Abstract: Correlates of procurement performance of Traditional and Labour-only methods are investigated. Purpose of this study is to investigate if procurement challenges, contractual procedures, designer's experience, building type and final contract sum have influences on the performance of both methods. 120 questionnaires were sent out to the various respondents who have used the two methods. 64 responses were received from 39 Traditional projects and 25 Labour-only projects. Results indicate that unit cost of Labour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(50 citation statements)
references
References 3 publications
2
37
0
Order By: Relevance
“…The factors influencing the choice of these procurement methods in the delivery of maintenance works are duration of project (time), the cost of the project, quality level, risk allocation, price competition and flexibility. These findings are to some extent similar to Oyegoke (2004), Ogunsanmi (2001) and Ogunsanmi and Bamisile (1997). In their survey of procurement methods, duration of the project, total cost of the project, quality according to specifications were ranked as the most influential factor in the choice of procurement methods, attributable to the volume of work to be maintained.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The factors influencing the choice of these procurement methods in the delivery of maintenance works are duration of project (time), the cost of the project, quality level, risk allocation, price competition and flexibility. These findings are to some extent similar to Oyegoke (2004), Ogunsanmi (2001) and Ogunsanmi and Bamisile (1997). In their survey of procurement methods, duration of the project, total cost of the project, quality according to specifications were ranked as the most influential factor in the choice of procurement methods, attributable to the volume of work to be maintained.…”
Section: Discussionsupporting
confidence: 89%
“…Oyegoke (2004) define procurement as the overall method used by a client/or representatives so as to arrive at a tender figure and other operation towards the selection of a contractor to deliver a project at an agreed time and conditions. According to Ogunsanmi (2001), the procurement process is also concerned with the form of procurement whether by contract or direct labour, and with the quality of delivery of both the work carried out and the level of service provided.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on mass housing attributes have indicated that MHPs exhibit unique procurement arrangements which underline the organizational attributes that make the management of MHPs require unique skills and management style [2,14]. The organizational features of MHPs are evidenced in its complex network of team relationship, multiple interdependent subcontracting under scheme, and complex network of procurement systems [4,6,15]. In the context of this study, the organizational task functions that characterize the procurement management attributes of MHPs are defined by the contract packaging, management concept for labour contracting and trade subcontracting, and coordination concept in subcontracting arrangement [2,6,15,18].…”
Section: Mass Housing Projects and Their Attributesmentioning
confidence: 99%
“…From a practical perspective, mass housing consulting teams may take the form of either a team composition where all members are from outside the developing organization or all from the organization and a mix of part from the organization and part from outside the organization. The procurement systems in contractor selection and subcontracting may also take the forms of Labour-Only and Direct-Labour and other discretionary procurements such as Alliancing, Partnering, Joint Ventures, and single or multilayered subcontracting [6,19,20]. These procurement styles come with their challenges in management and communication performance on the mass housing projects.…”
Section: Nature Of Procurement Systems (Ps) Features On Massmentioning
confidence: 99%
See 1 more Smart Citation